The associations between physical activity, screen time and weight from 6 to 14 yrs: The Raine Study - Hands, B.; Chivers, P.; Parker, H.; Beilin, L.; Kendall, Garth; Larkin, D. (Sports Medicine Australia, 2011)
To examine the strength and direction of the relationship between physical activity level, screen use and BMI in a cohort at ages 6, 8, 10 and 14 yrs as part of a prospective longitudinal cohort study. The sample comprised 1403 males and females who participated in the follow-up survey at 14 yrs of age between 2003 and 2005. Exploratory structural equation modelling was used to examine the interrelationships between physical activity level, BMI and screen time at 6, 8, 10 and 14 yrs. Predictors of BMI at 6, 8, 10 and 14 yrs explained 1.3, 76.1, 80.1 and 73.1 percent of the variances, respectively, with previous BMI the largest predictor [χ2 = 43.082, df = 36, p = 194]. Increased screen time predicted higher BMI and lower physical activity at 8 and 10 yrs but not 14 yrs. At 14 yrs, physical activity predicted BMI. Sedentary patterns of behaviour in early childhood were predictive of later and concurrent obesity, whereas physical activity was predictive of obesity in adolescence. Different intervention targets are required for children and adolescents.